On the driving force for crack growth during thermal actuation of shape memory alloys. (April 2016) - Baxevanis, T.; Parrinello, A.F.; Lagoudas, D.C.
Abstract: The effect of thermomechanically induced phase transformation on the driving force for crack growth in polycrystalline shape memory alloys is analyzed in an infinite center-cracked plate subjected to a thermal actuation cycle under mechanical load in plain strain. Finite element calculations are carried out to determine the mechanical fields near the static crack and the crack-tip energy release rate using the virtual crack closure technique. A substantial increase of the energy release rate – an order of magnitude for some material systems – is observed during the thermal cycle due to the stress redistribution induced by large scale phase transformation. Thus, phase transformation occurring due to thermal variations under mechanical load may result in crack growth if the crack-tip energy release rate reaches a material specific critical value. Abstract : Highlights: The effect of thermal actuation on the driving force for crack growth in SMAs is analyzed. The crack-tip energy release rate is identified as the driving force for crack growth. Cooling under constant load results in a substantial increase of the energy release rate. Thermal actuation under constant load may result in crack growth.